The effect of physical exercise on the spiritual well-being of older adults-mediating role of self-care ability - Meng Wang; Xiaolei Yang; Yanhong Su (PLoS ONE, 2026)
Purpose With the increasing aging of the population, older adults over the age of 65 constitute the largest and most rapidly expanding population group in the world, and the quality of survival of older adults is generally decreasing. A growing number of researchers have shown that physical exercise is positively associated with spiritual well-being and self-care ability in older adults, thereby affecting their health status and quality of life. The purpose of this study was to investigate the effect of physical exercise on the spiritual well-being of older adults and the mediating role of self-care ability. Patients and methods The research data collection period in this study was from June 8, 2024, to Sept 2024. We surveyed 405 urban older adults and used Pearson correlation coefficients to analyze the relationship between physical exercise, spiritual well-being, and self-care ability. Mediation analysis was used to explore the mediating role of self-care ability in physical exercise and spiritual well-being. Results Physical exercise is positively related to the spiritual well-being index and is related to the mediating effect of self-care ability. Conclusion This study shows that physical exercise is positively correlated with both spiritual well-being and self-care ability of the elderly, and affects the spiritual well-being index through the mediating effect of self-care ability. Physical exercise is a proactive behavior, which is conducive to enhancing the physical and spiritual health and well-being of the elderly under the advocacy of “active aging”.